Discovery of electromagnetic polarization in Asian rice wine deterioration process and its applications - Zhang, W; Cao, X; Cheng, X; Sun, D; Wei, T; Fang, Z; Li, J; Chen, F; Liu, X; Cai, Z; Shen, C (Public Library of Science, 2024)
Rice wine, known as yellow wine in China and Japan, possesses considerable nutritional value and holds significant global influence. This study addresses the challenge of preserving rice wine, which is prone to rancidity due to its low alcohol content. Conventional storage techniques employing pottery jars often result in substantial spoilage losses. Through rigorous investigation, this research identifies a polarization phenomenon exhibited by degraded rice wine when subjected to high-frequency microwaves(>60GHz), presenting a pioneering method for detecting spoilage, even within sealed containers. Employing a multi-channel microwave radar apparatus, the study delves into the susceptibility of rice wine to electromagnetic waves across various frequencies, uncovering pronounced polarization traits in deteriorated samples within the E-band microwave spectrum. Furthermore, lab-controlled simulations elucidate a direct correlation between physicochemical alterations and high-frequency Radar Cross Section (RCS) signals during the wine’s deterioration process. A novel six-membered Hydrated Cluster hypothesis is proposed, offering insights into the molecular mechanisms underlying this phenomenon. Additionally, dielectric property assessments conducted using vector network analyzers (VNA) reveal noteworthy enhancements in the dielectric constant of deteriorated rice wine, particularly within the high-frequency domain, thereby augmenting detectability. These findings carry implications for refining rice wine preservation techniques and contribute to the advancement of non-destructive testing technologies, enabling the detection of rice wine deterioration or indications thereof, even within sealed vessels.